IMPLEMENTASI MODEL PBL (PROBLEM BASED LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA - Prayogi, Saiful; Asy’ari, Muhammad (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
This research was aimed to improve the students’ learning achievement and critical thinking ability through problem based learning (PBL) model, the method which was applied in this research was classroom action research. It consisted of two cycles and each cycle consisted of planning, implementing, observing, and reflecting. The data was taken by giving the students test, it was in form of multiple choice test. The was used to know the students learning achievement to know students critical thinking, essay test was used. The finding of the research show that there was improvement from cycle to cycle. (1) at the first cycle: the percentage score of students mastery was 63.16% ; the mean score of the students critical thinking ability was 51.31 ; (2) at the second cycle : percentage score of the students mastery was 85% ; mean score of the students critical thinking ability was 72.08 and catagorized into critical and between 62.59 – 81.25. based on the finding, it can be concluded that problem based learning (PBL) model can improve the students learning achievement and critical thinking ability.